ANALISIS PEMBERITAAN ISU AKTIVITAS PERTAMBANGAN NIKEL DI KABUPATEN RAJA AMPAT MELALUI PERSPEKTIF AGENDA SETTING THEORY - M Hanif Kurniawan (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2025)
Climate change, a prominent global agenda in the last decade, has driven the adoption and implementation of green economic policies and sustainable development campaign by various nations. The Indonesian government, through its clean energy transition campaign, has promoted electric vehicle (EV) adoption to reduce carbon emissions. This initiative has spurred a new industrial market in Indonesia, supported by the government's nickel downstreaming policy, given nickel's critical role in the EV industry. However, nickel mining and its industries have demonstrated significant negative impacts on the environment and local communities, notably in Raja Ampat. This qualitative descriptive study, employing literature review and observational approach, found that intensive reporting by the press and activists via mass media and social media platforms regarding nickel mining activities in Raja Ampat effectively created a media agenda. This transformed into public agenda and subsequently a policy agenda within a short timeframe. The public pressure generated by this widespread response compelled the government to act in accordance with popular demand, leading to the temporary cessation of nickel mining activities in Raja Ampat. This research demonstrates implementing agenda-setting method within media activism can be an effective approach in crisis communication to efficiently garner public response and drive policy action.